Agriculture and the developing countries. The Soviet and Chinese models (N.pl., 1962)
The 1st part was publ. in The China Quarterly, 1961 (n ̊5, January- March). The 2nd part was publ. in the Proceedings of the Symposium on economic and social problems of the Far East, 1962.